Regulatory Challenges in the Face of the Gig Economy and Cross-Border Remote Work - R Pugu, Melyana; Sugiardi, Sigit; Thalib, Bahrun (Lafadz Jaya Publisher, 2025)
The development of the gig economy and cross-border remote work has significantly changed the face of the world of work but also poses complex regulatory challenges. This research aims to identify and analyse the regulatory challenges faced in the context of the gig economy and cross-border remote work and evaluate the policy responses from various countries. The method used is a literature review by examining scientific literature, national and international regulations, and related policy reports. The results showed that the unclear legal status of workers, differences in regulations between countries, taxation issues, and limited social protection are the main obstacles. This research recommends the need for adaptive regulatory reforms and international collaboration to create an inclusive and equitable legal framework to support sustainable growth of the digital economy and protect workers' rights.